Curricular and Co‐curricular Influences on Undergraduate Engineering Student Leadership. Issue 1 (7th January 2017) - Knight, David B.; Novoselich, Brian J.
Abstract: Background: Multiple reports call for undergraduate programs to develop engineers who have leadership abilities. Such preparation requires understanding how the undergraduate experience relates to student leadership abilities. Limited research has shown disagreement among faculty members and administrators about effective approaches for engineering leadership development. Purpose/Hypothesis: The purpose of this research was to understand what precollege characteristics and experiences, university experiences, and undergraduate engineering program contexts relate to undergraduate engineers' self‐reported leadership skills. Design/Methods: Using hierarchical linear modeling, this quantitative study examined the variance of students' self‐reported leadership skills as explained by their precollege characteristics and undergraduate experiences. The study drew from a nationally representative survey‐based dataset of 5, 076 undergraduate engineers from 150 undergraduate engineering programs from 31 colleges and universities. Results: Although multiple facets of the undergraduate experience significantly relate to students' self‐reported leadership skills, curricular emphases on core engineering thinking, professional skills, and broad and systems perspectives explain the greatest amount of variance. The lack of significant relationships at the program level suggests a lack of formal leadership development within the undergraduate curriculum at large. Conclusions: Results indicate that entrusting the leadership development of undergraduate engineering students to the co‐curriculum is an inefficient method of developing leadership skills for undergraduate engineers. The curriculum more strongly relates to engineering students' leadership skills. Identifying ways for faculty members to enhance this curricular focus could further development of technologically adept engineering leaders.